Middle Tech Software Work and the Culture of Good Enough - Bialski, Paula (Princeton University Press, 2024)
Why software isn't perfect, as seen through the stories of software developers at a run-of-the-mill tech companyContrary to much of the popular discourse, not all technology is seamless and awesome; some of it is simply "good enough." In Middle Tech, Paula Bialski offers an ethnographic study of software developers at a non-flashy, non-start-up corporate tech company. Their stories reveal why software isn't perfect and how developers communicate, care, and compromise to make software work-or at least work until the next update. Exploring the culture of good enoughness at a technology firm she calls "MiddleTech," Bialski shows how doing good-enough work is a collectively negotiated resistance to the organizational ideology found in corporate software settings.The truth, Bialski reminds us, is that technology breaks due to human-related issues: staff cutbacks cause media platforms to crash, in-car GPS systems cause catastrophic incidents, and chatbots can be weird. Developers must often labor to patch and repair legacy systems rather than dream up killer apps. Bialski presents a less sensationalist, more empirical portrait of technology work than the frequently told Silicon Valley narratives of disruption and innovation. She finds that software engineers at MiddleTech regard technology as an ephemeral object that only needs to be good enough to function until its next iteration. As a result, they don't feel much pressure to make it perfect. Through the deeply personal stories of people and their practices at MiddleTech, Bialski traces the ways that workers create and sustain a complex culture of good enoughness
Keywords: SOCIAL SCIENCE / Anthropology / Cultural & Social; Computer software -- Development